Smart materials for NZEB buildings. Adaptive technological solutions for sustainable projects - Rosa Romano (Agathón)
The paper shows some of the results of the European research COST Action TU 1403 Adaptive Envelope, whose aim is to map technological innovation at an international level, linked to design and creation of adaptive façades systems, by analysing the subsystems that from the micro to the macro scale allow to reach and exceed the energy-environmental targets foreseen by the current national and international regulations. Starting by analysing the state of the art, the paper will focus in particular on the subject of smart materials that can be used to create vertical closure systems with advanced screens, capable of improving indoor comfort and energy efficiency of new and existing buildings. Through the analysis of their material, technological and functional characteristics, will be defined the qualitative and performance parameters that influence their use and function on a full-scale.